Crecimiento regional versus la comunidad. Chiloé: un caso de autoconfianza colectiva regional - Abalos, José (Revista EURE - Revista de Estudios Urbano Regionales, 1985)
Based on the situation created years ago by the project known as "Astillas de Chiloé", this article explores the important issue related with regional social movements in Chile.